Modifies hummers method of graphene oxide nanostructures for fibre optic sensors application / Siti Rabizah Makhsin ... [et al.] - Makhsin, Siti Rabizah; Mohd Zali, Muhammad Izham Hakimi; Abdul Rani, Rozina; Saad, Nor Hayati; Ayub, Muhammad Azmi (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
For optical fibre sensors applications, nanomaterials have been widely used to enhance sensor performance. Here, the fibre optic uses the transmission of light by total internal reflection along with the fibre and depending on the diameter of the fibre and the wavelength of the light used. Among others, graphene oxide nanostructures (GO) would offer exceptional advantages on the sensing mechanism due to the 2D properties of the monocellular layer originally from graphite. The main objectives of this research are to successfully synthesis GO using a chemical reduction method known as modifies Hummer's method and later, deposited the GO onto the modified fibre optic layer to create a sensing platform. Before that, the standard plastic of fibre optic (POF) was modified by removing the cladding layer (1 cm) using a mechanical etching technique, thus the sensing platform can be created. The morphology and optical properties of the system were characterised using scanning electron microscopy (SEM) and ultraviolet-visible (UV-Vis) spectroscopy. The result of the preparation and characterisation of GO-optical fibre coatings was presented, considering its potential use for sensing applications. The stable GO was prepared by three hours of stirring time during the synthesis and a longer dipping time was preferred to fully coat the core of the exposed POF. Aiming to explore this scheme for sensing applications, GO-coated tilted fibre will be later measuring via refractive index variations. An improvement on the sensitivity should be obtained and thus become a promising sensing platform for the development of a new line of sensors.